1998
DOI: 10.3171/jns.1998.88.3.0478
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular shunt removal: the ultimate treatment of the slit ventricle syndrome

Abstract: A significant number of patients debilitated by SVS may experience improvement in their symptoms and undergo shunt removal according to this protocol, improving their quality of life and simplifying their medical follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(87 citation statements)
references
References 29 publications
0
86
0
1
Order By: Relevance
“…TV has been considered as an important strategy in the resolution of slit ventricle syndrome [10, 11], however, it has never been discussed as a treatment option for shunt-induced SDH. In these 2 patients with significant disturbance of consciousness, external ventricular drainage revealed the necessity for low-pressure drainage for clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…TV has been considered as an important strategy in the resolution of slit ventricle syndrome [10, 11], however, it has never been discussed as a treatment option for shunt-induced SDH. In these 2 patients with significant disturbance of consciousness, external ventricular drainage revealed the necessity for low-pressure drainage for clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…1 This observation by Professor Epstein was indeed true, but we had not recognized it as a criterion for ETV before his comments. In that paper 80% of patients whose ventricles had expanded at the time of shunt removal and clamping of the EVD and who did not have hydrocephalus related to spina bifida underwent successful ETV and were rendered shunt free.…”
Section: Selecting Patients For Etvmentioning
confidence: 98%
“…They also conceded the possibility of a tendency to hindbrain herniation, resulting from an LP shunt especially in patients with Chiari malformation. Recently, some successful trials reported methods to avoid this risk of herniation and other shunt complications, such as endoscopic third ventriculostomy, gradual elevation of intracranial pressure, and valve upgrade [9][10][11] . Although valve upgrade in patients with SVS which develops from PC may improve CSF drainage and improve SVS symptoms, the resultant increased intracranial pressure may have a higher risk of neural injuries and hindbrain herniation from the high intracranial pressure of long duration.…”
Section: Discussionmentioning
confidence: 99%
“…He also suggested appropriate modes of therapy such as medication, shunt removal or revision, valve upgrading, LP shunting, and cranial expansion surgery according to his classification. But there still exists controversy over which mode is the most efficacious since most studies to date have not objectively compared the various methods and only presented successful results of each mode independently [5,[8][9][10][11][19][20][21] . It would seem appropriate to perform cranial expansion surgery, including decompression surgery, in cases where after brain development restriction develops as a result of secondary craniosynostosis after shunting [19,20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation